CONSIDERATIONS OF A MEDIATOR IN PROVIDING RECOMMENDATIONS FOR THE SETTLEMENT OF INDUSTRIAL RELATIONS DISPUTES THROUGH MEDIATION : (STUDY OF DISDAGKERKOPUKM, KARANGANYAR DISTRICT) - Kurnianingsih, Marisa; Hanif Al Hafizh, Muhammad (DE'RECHTSSTAAT, 2024)
Industrial relations are a legal relationship between employers and workers/labourers or trade unions/labour unions. In industrial relations, rights disputes, conflict of interest, termination of employment, and trade/labour union disputes exist. This dispute usually occurs due to differences in views resulting in a dispute between the two. In its settlement, the Labor Office has a role in resolving industrial relations disputes, among other ways, through non-litigation or bipartite settlement (arbitration, conciliation, mediation). The related agency has made efforts to resolve this through mediation, which has several stages. The settlement process goal is an agreement between the two parties contained in a written recommendation issued by the mediator, namely a joint agreement (Perjanjian Bersama). If there is no agreement, the moderator will issue a written recommendation with full consideration, whose function is to continue carrying out the advanced settlement process at the Industrial Relations Court.